2014
DOI: 10.1363/4003914
|View full text |Cite
|
Sign up to set email alerts
|

Is Age Difference Between Partners Associated with Contraceptive Use Among Married Couples in Nigeria?

Abstract: An age difference between sexual partners is a social norm in most societies; typically, the man is older than the woman. The acceptability of unions in which the husband is considerably older than his wife is more variable, although relatively large age differences are found in patriarchal societies. Large age gaps are often accompanied by differences in maturity, life experiences, social position and financial resources, which may make relationships inherently unequal and a source of risk for women's health.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 35 publications
4
30
2
Order By: Relevance
“…It was expected that wife or husband reporting more children will encourage the use of contraceptive in a union because the partner who has more children would like to limit births in the current union, but this was not the case in Nigeria, supporting a previous finding in Nigeria by Ibisomi 16 . On the other hand, it is more likely that the partner who has more children would want to have children with the current spouse, but this depends on the number of children they have outside and in the current union, which is not available in the data used for this study.…”
Section: African Journal Of Reproductive Health December 2017; 21 (4)mentioning
confidence: 72%
See 1 more Smart Citation
“…It was expected that wife or husband reporting more children will encourage the use of contraceptive in a union because the partner who has more children would like to limit births in the current union, but this was not the case in Nigeria, supporting a previous finding in Nigeria by Ibisomi 16 . On the other hand, it is more likely that the partner who has more children would want to have children with the current spouse, but this depends on the number of children they have outside and in the current union, which is not available in the data used for this study.…”
Section: African Journal Of Reproductive Health December 2017; 21 (4)mentioning
confidence: 72%
“…Zambia has less than 2% of couples who had no education, unlike Nigeria where slightly above a quarter had no education. The positive association between spousal education difference and contraceptive use stresses the importance of education in behavior modification toward uptake of contraceptives by couples 16,18,21,22 . Couples who are not educated are not likely to know the benefits of optimal spacing and limiting childbearing.…”
Section: Discussionmentioning
confidence: 99%
“…Ideational or psychosocial variables have also been found to be strongly associated with contraceptive use, including perceived self-efficacy to take actions related to contraceptive use, spousal communication about family size and contraceptive use, perceived social approval of contraception, ideal family size, and misconceptions about contraceptives and family planning (Okigbo et al 2017;Babalola et al 2015;Babalola 2017;Gueye et al 2015;Ankomah, Anyanti, and Oladosu 2011;Avidime et al 2010;Tumlinson et al 2013). Studies have also found male partners' characteristics to be associated with contraceptive use, including age, education, and family size desires (Ejembi et al 2015;Oyediran, Ishola, and Feyisetan 2002;Ibisomi 2014). Furthermore, women's autonomy and decision-making agency have been positively linked with contraceptive use (James-Hawkins et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that husband's with secondary and tertiary education level had more influence on FP, whereby they prefer to choose male sterilization and condoms (gubhaju 2009). Moreover, education level can influence the decision making on the use of contraceptive as a FP method (Hamid et al 2011;Ibisomi 2014). …”
Section: Husband's Educationmentioning
confidence: 99%